Laduni Science in Q.S. Al-Kahf [18] : 65 (Comparative Study of Tafsir Al-Munir Marah Labid and Al-Mishbah) - Wahyudi, Dedi; Prasetiawati, Eka; Amin, Muhammad Nur (JASNA : Journal For Aswaja Studies, 2025)
Laduni science has long been recognized within society, often perceived as a form of knowledge granting its possessor an infallible grasp of truth and insight into unseen realities. However, this perception is overly simplistic, as individuals endowed with laduni knowledge are not inherently free from error nor exempt from the need for continuous learning and self-improvement. This study examines the interpretation of laduni knowledge, explores its differing and overlapping perspectives, and analyzes its Sufi and socio-socialist orientations based on the term ladunna 'ilman in Q.S. Al-Kahf [18]: 65. Using a comparative approach, the study contrasts the Tafsir al-Munir Marah Labid, employing a global (ijmali) method with a Sufi emphasis, and the Tafsir al-Mishbah, characterized by an al-Adabi al-Ijtima'i style. Findings reveal that laduni knowledge aligns with scientific principles and is amenable to rational explanation.